1982
DOI: 10.1159/000156044
|View full text |Cite
|
Sign up to set email alerts
|

Control Role of an Adult Male in a Captive Group of Lowland Gorillas

Abstract: An adult male gorilla was removed from the social group in which it had resided for 27 months. There was an immediate increase in aggressive behaviors among the remaining adult females, as well as an intensification of mother-infant social behaviors. The return of the male resulted in an immediate rise in male aggression and a decline in female aggression, with a gradual return to baseline levels in most behaviors. The control role of the male in the group through aggressive behaviors is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In captivity, Hoff et al [1982] found that after removal of a silverback male, there was an immediate increase in aggression among the remaining females, which only declined about a week after the male's return. After reintroduction, the male's aggressive behavior initially increased to frequencies far above his pre-removal level, and only gradually returned to baseline [Hoff et al, 1982]. Nadler and Miller [1982] found a direct relationship between levels of male aggression and sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In captivity, Hoff et al [1982] found that after removal of a silverback male, there was an immediate increase in aggression among the remaining females, which only declined about a week after the male's return. After reintroduction, the male's aggressive behavior initially increased to frequencies far above his pre-removal level, and only gradually returned to baseline [Hoff et al, 1982]. Nadler and Miller [1982] found a direct relationship between levels of male aggression and sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Following the introduction of the new male, there was a slight peak in non-contact aggression. In a previous captive study, female-female aggression increased significantly after the removal of the silverback, but returned to baseline levels within 2 weeks of his reintroduction [Hoff et al, 1982].…”
Section: Discussionmentioning
confidence: 69%
“…In a study of captive western lowland gorillas, Hoff et al [1982] found a significant increase in female-female aggression following the removal of the silverback. Upon his return, the silverback repeatedly displayed and charged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like wild mountain gorillas, in captive lowland gorilla groups older females that have lived in the group the longest are dominant to younger females [Scott and Lockard, 1999]. The silverback male serves to mediate intragroup aggression and stabilize social relationships among group members [Hoff et al, 1982[Hoff et al, , 1998]. The presence of the silverback male is important to facilitate the integration of hand-reared infants into established social groups [Meder, 1990a;McCann and Rothman, 1999].…”
Section: Introductionmentioning
confidence: 99%